2023
DOI: 10.3390/horticulturae9030334
|View full text |Cite
|
Sign up to set email alerts
|

Horticultural Activities Participation and College Students’ Positive Mental Characters: Mediating Role of Academic Self-Efficacy

Abstract: In recent years, the ongoing impact of the COVID-19 epidemic, irregular closed school life and frequent online teaching have negatively impacted the mental health and academic performance of many college students. Doing horticultural activities is an effective way to promote physical and mental health and enhance academic performance. This paper explores the relationship between horticultural activities participation, academic self-efficacy and positive mental characters under the perspective of disciplinary i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…By observing their own successful experiences, individuals believe in their ability to cope with difficulties and develop problem-solving skills. This confidence and expectation contribute to further enhancing individuals' self-efficacy (Guo et al, 2023;Lu et al, 2023).…”
Section: The Role Of Horticultural Therapy In Self-cognitionmentioning
confidence: 98%
See 1 more Smart Citation
“…By observing their own successful experiences, individuals believe in their ability to cope with difficulties and develop problem-solving skills. This confidence and expectation contribute to further enhancing individuals' self-efficacy (Guo et al, 2023;Lu et al, 2023).…”
Section: The Role Of Horticultural Therapy In Self-cognitionmentioning
confidence: 98%
“…For example, incorporating green plants in office or study spaces has been shown to reduce stress and improve productivity (Li et al, 2022). In addition, horticultural activities cultivate individuals' sense of self-efficacy and mastery through the processes of creativity and problem-solving, thereby building their confidence and resilience (Guo et al, 2023;Lu et al, 2023).…”
Section: The Role Of Horticultural Therapy In Stress Reductionmentioning
confidence: 99%